(untitled) (Neo Scientific Peer Reviewed Journal, 2023)
The issue of treatment of critical ischemia of the lower extremities today is one of the main and most urgent problems of surgery. Unsatisfactory results of performed amputations of the lower extremities due to critical ischemia on the background of diabetes mellitus determine the relevance and social significance of studying the issues of prevention of amputations of the lower extremities using modern endovascular interventions, which indicates the need to optimize the tactics of surgical treatment. Improving the results of treatment of patients with critical lower limb ischemia in diabetic foot syndrome through a differential treatment approach, taking into account endovascular interventions, is the main goal. The question of the treatment of critical ischemia against the background of diabetes mellitus remains open and requires an active solution.